KRAS promotes tumor metastasis and chemoresistance by repressing RKIP via the MAPK–ERK pathway in pancreatic cancer. Issue 11 (21st January 2018) - Yang, Kege; Li, Yaqing; Lian, Guoda; Lin, Haoming; Shang, Changzhen; Zeng, Linjuan; Chen, Shaojie; Li, Jiajia; Huang, Chumei; Huang, Kaihong; Chen, Yinting
Abstract : Oncogenic KRAS plays a crucial role in pancreatic ductal adenocarcinoma (PDAC) development and progression. However, the mechanism has not been clearly elucidated. RKIP is a tumor repressor, and loss of RKIP has been shown in PDAC. Here, we found that KRAS expression was inversely correlated with RKIP expression in PDAC fresh tissue regardless of the KRAS mutant status. The negative correlation between KRAS and RKIP was further confirmed in our PDAC tissue microarray. KRAS overexpression and RKIP downregulation were associated with poor clinical outcomes. Knockdown or overexpression of KRAS in PDAC cell lines robustly increased or decreased, respectively, RKIP protein and mRNA levels. Furthermore, the MAPK–ERK pathway was involved in the regulation of RKIP. KRAS‐regulated RKIP expression, which in turn affected the expression of pivotal epithelial–mesenchymal transition (EMT) and apoptosis factors. The biological function of the KRAS–RKIP axis was demonstrated in human pancreatic cancer cells in vitro and in vivo . KRAS knockdown increased RKIP expression and inhibited metastasis and chemoresistance. Moreover, the feature of metastasis and chemoresistance was rescued in the KRAS‐knockdown cells through the inhibition of RKIP by RNA interference. In conclusion, our studies demonstrate how KRAS inhibits the tumor suppressor RKIP, thus offering novel justification for targeting RKIP as a strategy to overcome KRAS‐induced tumor metastasis and chemoresistance in PDAC. Abstract : What's new? The majority of pancreatic ductal adenocarcinomas (PDACs) are characterized by dysfunctional KRAS activation, which leads to persistent activation of downstream tumor‐promoting pathways. The mechanisms underlying the activation of these pathways are not fully known. In this analysis of pancreatic cancer cells and PDAC patient tissues, KRAS expression was found to be inversely correlated with expression of Raf kinase inhibitory protein (RKIP). KRAS was further found to regulate RKIP via activation of the ERK signaling pathway. In mice, injection of KRAS‐silenced pancreatic cancer cells resulted in attenuated tumor growth and increased chemosensitivity. These effects were abolished by ablation of RKIP expression.